Product review on the monoclonal antibody palivizumab for prevention of respiratory syncytial virus infection - Bernhard Resch (Taylor & Francis Group, 2017)
Respiratory syncytial virus (RSV) accounts for about 20% of all respiratory infections in children below the age of 5 y. It is associated with up to 63% of all acute respiratory infections and up to 81% of all viral lower respiratory tract infections causing hospitalization in infants and young children. RSV leads to seasonal epidemics between November and April in the northern hemisphere. Most severe infections (RSV accounts for 50 to 80% of all cause bronchiolitis) affect infants younger than 6 months of age and high-risk infants including those born preterm with or without bronchopulmonary dysplasia and those with hemodynamically significant congenital heart disease up to an age of 24 months. Palivizumab, a highly potent RSV-neutralizing monoclonal antibody (Mab), has been licensed in 1998 for prophylactic use to prevent RSV associated hospitalizations in high-risk infants. This Mab is given by monthly intramuscular injection at a dose of 15 mg/kg over the RSV season (up to 5 times). Palivizumab proved to be safe and well-tolerated in this population. Concerns have been raised regarding cost-effectiveness of palivizumab and thus, palivizumab prophylaxis is mainly limited to selected high-risk infants for the first RSV season. Long-lasting Mabs will be the next future approach in the prophylaxis of RSV hospitalization until a vaccine is developed.